Malaysia Airlines Berhad - Chai Yuan Ping; Daisy Mui Hung Kee; Chai Yee Ling; Chew Shi Xian; Wong Chun Sian; Yusef Hamad Alnasser (International Journal of Tourism and Hospitality in Asia Pasific, 2019)
MAS Airlines was branded as Malaysia Airlines and known as the second big airlines' company in Malaysia. We choose MAS Airlines as our targeted company in this project due to the huge information can be accessed on the Internet and the issues that go through by MAS Airlines in this few years. We have accessed the current issue faced by our targeted company, MAS Airlines. According to our research, we found out that the company is having difficulties in competing with the competitors, facing unprofitability and failed to turnover and managing its technical capacity. Problems identified were flight MH001, an Airbus from London to Malaysia which forced to turn back more than an hour, MH134 which returned to Brisbane due to misplacement of plastic covers and the emergency landing of MH122. We followed our findings by investigating the reasons for those tragedies from happening. Since the airline had undergone top management handover, the company is obviously struggling with staff engagement. From a factual perspective, the airline is currently experiencing losses continuously for 3 years which ended up with dramatic RM1 billion losses when implementing a restructuring plan. High operation expenditure such as excessive high salary paid to top management is believed to be the dominating cause. Besides, extreme cash outflow due to the purchase of an aircraft was also regarded as a bad investment. MAS Airlines should be reconstructed and rebuilt after going through some critical issues in order to back to the top status as before by conducting the effective policies.